REPRODUCTIVE DYNAMICS of THE MAIN SPECIES of FISH IN THE MUNICIPAL RESERVOIR of SAO JOSE do RIO PRETO - Linhares de Andrade, Vanessa Xavier [UNESP]; de Faria e Souza Campos, Fabio [UNESP]; Langeani, Francisco [UNESP]; Romagosa, Elizabeth (Inst Pesca, 2008)
The objective of this study was to investigate the reproductive dynamics of fish of the Characidae (Serrapinnus notomelas, Hemigrammus marginatus, Hyphessobrycon eques, Piabina argentea, Steindachnerina insculpta) and Poecilidae (Poecilia reticulata) families in the municipal reservoir of Sao Jose do Rio Preto, SP, Brazil. The populational structure was evaluated with regard to sex ratio, classes of length, and the estimate of the mean size of the specimens at first maturation, from February 2002 to January 2003. The sex ratio was similar for S. notomelas, H. eques and P. argentea. However, for the other three species, the difference between males and females was higher than 5%. The captured species, with the exception of P. argentea, exhibited significant differences between the sexes in the month that follows the rain season. It was also verified that the males of the studied species, with the exception of P. reticulata, were predominant in the lower classes of length. For S. notomelas, H. eques and S. insculpta, the males showed higher values of L(50) than the females, the opposite of what occurred with the only species of Poecilidae captured, possibly because they are viviparous and keep the embryos in their abdominal cavity.
Keywords: Characidae; First Maturation; Populational Structure; Reproductive Dynamics; Reservoir; Poecilidae